The Effect of Starch-Lactose Filler Ratio on the Quality Characteristics of Meniran Extract Capsule - Kawiyanto, Joko; Elina, Alifah Asri; Sasongko, Jessica Herlin Labella (Clinical and Pharmaceutical Sciences Journal, 2025)
The empirical utilization of medicinal plants by Indonesians has long been known as "jamu". Meniran (Phyllanthus niruri Linn) is a plant containing phyllantin and hypophyllantin which have immunostimulant activity and potential for development into traditional medicine. This study aims to determine the influence of the starch-lactose filler ratio in the formulation of meniran extract herbal powder for the development of traditional medicine capsule preparations. The research was conducted experimentally using four meniran herbal powder formulas with variations in the starch-lactose filler ratio: 100%:0 (M1); 73%:27% (M2); 50%:50% (M3); and 27%:73% (M4). Based on the physicochemical properties of the powder, the most optimum formula was selected and evaluated for the quality of meniran extract capsule based on the requirements of the Indonesian Food and Drug Monitoring Agency, including organoleptic tests, flowability, loss on drying, and disintegration time. The results of this study show that variations in the starch-lactose filler ratio affect the moisture content of meniran herbal powder. Formula M2 with a starch:lactose filler ratio of 73:27 exhibited flowability that meets the requirements for development into traditional medicine capsules. Lactose at a concentration of 10% can be combined with starch as a filler and produce good loss on drying and disintegration time values.